2020
DOI: 10.1111/pcmr.12945
|View full text |Cite
|
Sign up to set email alerts
|

Connexins in melanoma: Potential role of Cx46 in its aggressiveness

Abstract: The skin is the largest organ in the human body, and it is constantly exposed to environmental insults, such as bacteria, viruses, air/water pollution, sunrays (Rodrigues et al., 2019). Three layers compose the skin: the epidermis, the dermis, and the hypodermis (Debeer et al., 2013). The epidermis is the outer layer of the skin, and it is the first barrier that protects the organism from external elements. Keratinocytes, melanocytes, Langerhans cells, and Merkel cells, arranged in five cellular layers, compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 171 publications
(216 reference statements)
0
13
0
Order By: Relevance
“…Lack of connexins was associated with development of chemical‐ and radiation‐induced tumours, 7,8 while reintroduction of connexins was shown to decrease tumorigenic behaviours 9 . Recently, Tittarelli and coworkers identified connexin 43 (Cx43) as an important key player in melanoma development and suggested the use of compounds that selectively enhance connexin expression for melanoma therapy 12 . For example, all‐trans retinoic acid (ATRA), an analogue of vitamin A, is currently being studied extensively for its potential as a therapeutic and chemopreventive agent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lack of connexins was associated with development of chemical‐ and radiation‐induced tumours, 7,8 while reintroduction of connexins was shown to decrease tumorigenic behaviours 9 . Recently, Tittarelli and coworkers identified connexin 43 (Cx43) as an important key player in melanoma development and suggested the use of compounds that selectively enhance connexin expression for melanoma therapy 12 . For example, all‐trans retinoic acid (ATRA), an analogue of vitamin A, is currently being studied extensively for its potential as a therapeutic and chemopreventive agent.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, both GJB5 (gap‐junction protein, Beta 5, Cx31·1) and GJB2 (gap‐junction protein, Beta 2, Cx26) were significantly downregulated in metastases compared with vertical growth phase melanomas (VGPM). GJB2 expression in melanoma tissue has been shown to promote a metastatic cell phenotype and enhance the establishment of new tumour niches through cell‐to‐cell communication with the surrounding tissue 12 . Regarding GJB5, a recent report has shown that it acts as a key regulator of migration and invasion in lung cancer cells, 14 although no specific study on GJB5 in melanoma has been published so far.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cx26, Cx43, Cx46) impacts cancer progression, and their targeting in vitro suggests their potential as therapeutic targets. 7,8 Even if the study of Scatolini et al does not further provide a functional role for GJB5 in melanoma carrying a BRAF mutation, the authors show that low expression of GJB5 inversely correlates with BRAF V600E in tissues and cultured melanoma cells. Short or long treatments with BRAF inhibitors and MAPK kinase inhibitors restored the expression of GJB5 in cells.…”
mentioning
confidence: 98%